An Exploration of English Language Learning Using E-Learning at Senior High Schools in Pontianak Regency - Hafizh, Aimar; Hafis, Maliqul; Aunurrahman, Aunurrahman; Sahrawi, Sahrawi; Purwiyanti, Purwiyanti (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2025)
This research explores the implementation of e-learning in English language teaching at senior high schools in Pontianak Regency. The study aims to investigate how e-learning is applied, understand students' perceptions of its use in English classes, and identify its strengths and weaknesses. Using a mixed-method approach, data were collected through questionnaires, interviews, and documentation involving two schools, SMK N 5 Pontianak and SMK S PGRI Pontianak. The findings indicate that e-learning is widely used for material sharing, assessments, and communication, with platforms like WhatsApp, Google Classroom, and Quizizz being the most utilized. While students and teachers recognize the flexibility and accessibility of e-learning, challenges such as limited interaction, technical issues, and lack of variety in teaching methods were noted. Despite these obstacles, both students and teachers generally perceive e-learning as a valuable tool in supporting English learning. Recommendations include improving infrastructure, diversifying learning platforms, and providing more training to enhance the effectiveness of e-learning. This research contributes to the development of innovative digital learning strategies and offers insights for optimizing e-learning in educational contexts.